Investment policy of Ukraine during full-scale war: immediate measures and future perspectives - Husieva, Nataliia; Niemets, Oleksii (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Problem definition. Solving the problems of an unfavorable investment climate and attracting the necessary investment resources for the reconstruction and recovery of Ukraine is impossible without implementing a thoughtful and effective investment policy. The purpose of the article. Objective of the article is to analyze Ukraine’s investment policy in conditions of full-scale Russian aggression and to justify possible directions for its improvement based on modern foreign approaches. Results, scientific novelty, practical significance. Over the past two years, Ukraine has taken several important steps that, even in the conditions of a full-scale war, ensure the inflow of investments into the state’s economy (4.25 billion in 2023). Firstly, priority sectors and industries for stimulating investment have been identified. These sectors ensure the livelihoods of citizens and strengthen the state’s defense capabilities and, in the future, will become the locomotive for the recovery of the Ukrainian economy. Among them are military-tech (high-tech weapons), metallurgy, mining, and mechanical engineering; agriculture and food industry; IT sector and startups. Additionally, the energy sector, construction industry, retail, housing, and communal services, and production engaged in mobilization orders, medicine, are extremely important. Secondly, a series of measures have been taken to insure investments against war risks: 1) agreements on risk insurance from international organizations with such practices, particularly the Multilateral Investment Guarantee Agency (MIGA) and the International Finance Corporation (IFC); 2) support from partner countries that provide guarantees to their businesses investing in Ukraine (from the USA, Poland, Germany, the United Kingdom, Denmark, and others); 3) a bill on insurance of investments (including domestic ones) against war and political risks through the Export Credit Agency of Ukraine (ECA). Thirdly, work has been done to provide investors with reliable information about the country’s investment potential, including creating an information platform for attracting foreign investments "Advantage Ukraine," which gathers over 500 investment projects and opportunities worth over 400 billion in ten economic sectors. Fourthly, the investment activity infrastructure is constantly developing and improving. The Government of Ukraine pays special attention to industrial parks, for the use of which foreign investors are offered significant tax benefits. As of 2024, there are 76 industrial parks in Ukraine. Among other measures of state investment policy are the resumption of privatization, deepening deregulation processes, harmonization of Ukraine’s current legislation with EU norms, particularly regarding the improvement of the customs and tax systems, creating conditions for quick investments, amending the law on so-called "investment nannies," expanding the range of potential investors, etc. Also, several important steps have been taken that positively impacted the state’s investment image. Ukraine acquired the status of an EU candidate member; the EU countries and some other countries canceled tariffs and quotas on Ukrainian exports; a transport visa-free regime with the EU was introduced; deferral of tax and customs payments, as well as reporting submission, was implemented; digitization of public services was carried out; the Ukrainian energy system was included in the unified European energy system; Ukrainian businesses demonstrated a high level of flexibility and adaptability, and the country – high resilience and loyalty, etc.